The impact of sodium reduction on overall nutrient content in Child and Adult Care Food Program meals - Elise Gahan; Elinor Hansotte; K Elise Lindstrom; Shelley Vaughn; Sandra Cummings (Cambridge University Press, 2023)
Abstract Objective: To understand the impact of Na reduction on the nutrient content of Child and Adult Care Food Program (CACFP) meals served through At-Risk Afterschool Meals (ARASM) without compromising the nutritional quality of the meals served. Design: Sodium Reduction in Communities Program (SRCP) partnered with a CACFP ARASM programme from October 2016 to September 2021. We assessed changes in Healthy Eating Index 2015 (HEI-2015) food component scores and macro- and micronutrients using cross-sectional nutrient analyses of October 2016 and 2020 menus. Setting: ARASM programme sites in Indianapolis, IN, USA. Participants: October 2016 and 2020 menus from one CACFP ARASM programme. Intervention: Na reduction strategies included implementing food service guidelines, modifying meal components, changing procurement practices and facilitating environmental changes to promote lower Na items. Results: From baseline in 2016 to 2020, fifteen meal components were impacted by the intervention, which impacted 17 (85 %) meals included in the analysis. Average Na per meal reduced significantly between 2016 (837·9 mg) and 2020 (627·9 mg) (P = 0·002). Between 2016 and 2020, there were significant increases in whole grains (P = 0·003) and total vegetables (P < 0·001) and significant reductions in refined grains (P = 0·001) and Na (P = 0·02), all per 1000 kcal served. Conclusions: This study demonstrates that Na content can be reduced in CACFP meals without compromising the nutritional quality of meals served. Future studies are needed to identify feasible best practices and policies to reduce Na content in the CACFP meal pattern.